KINETICS AND OXIDATION OF THE REACTIONS BETWEEN DITHIONITE ION AND NITROCELLULOSE IN ACIDIC PHASE - UMORU, PATRICIA; EFFIONG, UDOH (FUDMA JOURNAL OF SCIENCES, 2022)
Kinetics and oxidation of the reactions between dithionite ion and nitrocellulose was studied in acidic phase under the condition of excess [S2O42-] at T = 29 Â± 1oC, [H+] = 1.0 Ã— 10-2 mol dm-3, I = 1.0 mol dm-3 (Na2SO4) and Î»max = 360 nanometer. The oxidation-reduction reasult for NC+ with dithionite ion displayed a 1:2 mole ratio. The reaction showed first order in terms of the oxidant [NC+] as well as first order in terms of the reductant [S2O42-]. The rate of reaction indicated a first order relationship in terms of acid ion concentration. The reaction rate law is given as: k2 = a + b [H+] where a = Intercept, b = Slope. The rate of reaction increased with an increase in the moles of sulphuric acid added. This implies great stability of NC+ in an aqueous acidic medium. The rate decreased with an increase in sodium sulphate concentration. The spectroscopic investigation gave no signal for the formation of an intermediate complex. Based on the results obtained for the non-formation of intermediate complex, a plausible mechanism that favoured the outer-sphere mechanism was proposed for the studied reaction.